Orthorexia in Athletes: A Comprehensive Review of its Causes, Impact on Health, and Prevention Strategies - Fuczyło, Kamila; Stankevič, Karolina; Chernysh, Anna-Mariia; Dusińska , Aleksandra; Waszczyński, Jakub; Woźniak , Justyna; Kmieć, Justyna Weronika; Biesiada, Wiktor; Kopczyńska , Ewelina; Kulej, Piotr (Quality in Sport, 2025)
Aim: This review aims to explore the prevalence, causes, health impacts, and management strategies for orthorexia nervosa (ON) in athletes, with a focus on the challenges posed by the lack of standardized diagnostic criteria and the demands of sports that emphasize weight control, physique, and performance. Materials and Methods: The analysis is based on a synthesis of existing literature from medical and sports journals, focusing on studies that examine the relationship between ON and factors such as gender, BMI, athletic discipline, and the duration of physical activity. Special attention is given to studies evaluating multidisciplinary approaches to treatment and prevention. Results: Athletes, especially those in weight-sensitive and aesthetic sports, exhibit a higher prevalence of ON compared to non-athletes, with female athletes being particularly vulnerable. ON is driven by societal, cultural, and sports-specific pressures, leading to restrictive dietary practices that can cause nutrient deficiencies, metabolic imbalances, energy depletion, and psychological distress. Research findings on the relationship between ON, BMI, and gender are inconclusive, but athletes engaging in over 150 minutes of weekly physical activity, particularly endurance sports, are at higher risk. Conclusions: ON poses significant risks to both health and performance in athletes. Early diagnosis and a multidisciplinary treatment approach that integrates psychotherapy, dietary counseling, and nutritional education are critical for managing ON. Preventive measures at the organizational level, emphasizing balanced nutrition and collaboration among coaches, dietitians, psychologists, and physicians, are essential to reducing the prevalence of ON and promoting athlete well-being.